2019
DOI: 10.1111/ocr.12300
|View full text |Cite
|
Sign up to set email alerts
|

Dental arch relationship outcomes for children with complete unilateral and complete bilateral cleft lip and palate in New Zealand

Abstract: Objectives: To evaluate dental arch relationships of patients with complete unilateral and complete bilateral cleft lip and palate (CUCLP/CBCLP) in New Zealand. Setting and sample population: Retrospective nationwide observational outcomes study involving 100 CUCLP and 32 CBCLP non-syndromic patients. Material and methods: Four calibrated assessors, blinded to the origin of the randomized digital models, used the GOSLON (UCLP) and the Bauru-BCLP (BCLP) Yardsticks and a 100 mm visual analogue scale (VAS) (UCLP&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Continuing to monitor dental arches can be done by assessing the occlusal index. This evaluation is essential for the follow‐up of primary plastic surgeries (cheiloplasty and palatoplasty) and also for the evaluation of future treatments 26 . Thus, the hypothesis studied was partially accepted since the evaluation between the groups showed that there was a decrease in transversal and anteroposterior linear measurements, but not in area and volume.…”
Section: Discussionmentioning
confidence: 99%
“…Continuing to monitor dental arches can be done by assessing the occlusal index. This evaluation is essential for the follow‐up of primary plastic surgeries (cheiloplasty and palatoplasty) and also for the evaluation of future treatments 26 . Thus, the hypothesis studied was partially accepted since the evaluation between the groups showed that there was a decrease in transversal and anteroposterior linear measurements, but not in area and volume.…”
Section: Discussionmentioning
confidence: 99%
“…The Eurocleft studies showed the importance of intercenter comparisons and started to relate volume and outcomes [ 12 ]. This certainly informed the need for CSAG in the United Kingdom, and the subsequent “Americleft” [ 18 ] and New Zealand studies [ 19 , 20 ] followed similar lines. In New Zealand, where there are 100 cleft births a year, patients are treated in five centers; some outcomes are very poor and a centralized model is the most obvious way forward.…”
Section: Centralization Of Care and Researchmentioning
confidence: 90%
“…The assessment of behavior and QoL in children with OFC was undertaken as part of a broader research program of cleft outcomes in NZ. A more detailed description of other aspects of the study is available in previous publications (Fowler, Al-Ani et al, 2019;Fowler, Keall et al, 2019;Fowler, Wholley et al, 2019;Thompson et al, 2019;Fowler et al, 2020). Eligibility included all children with OFC considered to be nonsyndromic and born after January 1, 2000.…”
Section: Methodsmentioning
confidence: 99%